Applying incremental learning in binary-addition-tree algorithm in reliability analysis of dynamic binary-state networks - Hao, Zhifeng; Yeh, Wei-Chang (Reliability engineering & system safety, 2025)
This paper presents a novel approach to enhance the Binary-Addition-Tree algorithm (BAT) by integrating incremental learning techniques. BAT, known for its simplicity in development, implementation, and application, is a powerful implicit enumeration method for solving network reliability and optimization problems. However, it traditionally struggles with dynamic and large-scale networks due to its static nature. By introducing incremental learning, we enable the BAT to adapt and improve its performance iteratively as it encounters new data or network changes. This integration allows for more efficient computation, reduces redundancy without searching for minimal paths and cuts, and improves overall performance in dynamic environments. Experimental results demonstrate the effectiveness of the proposed method, showing significant improvements in both computational efficiency and solution quality compared to the traditional BAT and indirect algorithms, such as MP (minimal path) -based algorithms and MC (minimal cut) -based algorithms.